An approach to modeling impact energy absorption by surfaces - Davidson, P. L.; Wilson, S. J.; Wilson, B. D.; Chalmers, D. J. (Journal of Applied Biomechanics, 2009)
The energy return characteristics of an impacted surface are important for human impacts such as a child falling onto a play surface or an athlete landing on a gymnastic mat. The amount of energy dissipated or returned to the impacting body will contribute to the surface`s injury-minimizing or performance-enhancing potential. We describe a simple approach for selecting a rheological computer model to simulate a human-surface impact. The situation analyzed was of a head form impact onto gymnastic tumbling mats. The approach can be used to characterize other surfaces and impacts. The force-time-displacement characteristics of the mats were determined from laboratory drop tests. Various spring-damper models were evaluated for their ability to reproduce the experimental acceleration- time and force-displacement impact curves. An exponential spring and depth damper combination was found to best replicate the surface characteristics of the mats tested here, and to demonstrate their energy flow and exchange properties. Rheological modeling is less complex than finite element modeling but still accounted for the depth, velocity, and energy characteristics of the impacted surfaces. This approach will be useful for reproducing the characteristics of surfaces when the impacting body cannot be instrumented, and for predicting force and energy flow in nonrigid impacts.